Pancreatic pseudocysts: Therapeutic guidelines - Larre Borges, Uruguay; Delgado, Bolivar (Cirugía del Uruguay, 1971)
The paper analyzes the definition of this disease, followed by consideration of the surgical tactics employed and a discusston on the valué of the different methods for treating pancreatic pseudocysts according to their size, location and canalicular communication.